Type 2 diabetes - Boyko, Edward (Henry Stewart Talks, 2013)
Epidemiology of Type 2 Diabetes, Diabetes Risk Factors, Pathophysiology of Type 2 Diabetes, Progression of Type 2 Diabetes, Insulin Resistance, Secretion, and Diabetes Risk, Insulin Response during Glucose Tolerance Testing, Mechanisms of Type 2 Diabetes, Obesity Trends, Obesity and Diabetes Prevalence in Select Nations, Measures of Adiposity and Ethnicity, BMI Equivalents by Ethnicity, Measures of Central Adiposity, Japanese American Community Diabetes Study, Risk of Diabetes by Subcutaneous and Visceral Fat Areas, Ectopic Fat Deposition Hypothesis, Body Composition Does Not Explain Ethnic Risk Disparity, Changing Body Fat Distribution, Diabetes Prevention Program (DPP), DPP Results, Type 2 Diabetes Risk, Genes or Environment?, Single Nucleotide Polymorphisms of Interest, Genotype Score Distribution by Diabetes Outcome, Diabetes Risk by Genotype Score